2022
DOI: 10.3389/fcimb.2022.1014530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of patient with leptospirosis: A multicenter retrospective analysis in south of China

Abstract: PurposeLeptospirosis is a zoonotic disease caused by pathogenic spirochetes of the genus Leptospira. However, there is currently no consensual definition or diagnostic criteria for severe and different forms of leptospirosis. Therefore, more insight on clinical manifestations, risk factors, and outcomes of leptospirosis is warranted. The identification of leptospirosis with distinct clinical manifestations and prognosis in our population.MethodsMultiple correspondence analysis and hierarchical classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
4
4
Order By: Relevance
“…In contrast with previous clustering studies ( 5 , 15 ), our main finding was the identification of only three clinical clusters that we named: “the Weil’s disease” group (cluster 1), the “neurologic leptospirosis” group (cluster 2), and the “multiple organ failure” group (cluster 3). These clinical phenotypes are associated with different ICU outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous clustering studies ( 5 , 15 ), our main finding was the identification of only three clinical clusters that we named: “the Weil’s disease” group (cluster 1), the “neurologic leptospirosis” group (cluster 2), and the “multiple organ failure” group (cluster 3). These clinical phenotypes are associated with different ICU outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…The clinical pattern is pleomorphic, and the only specific entity described is an association between ARF and hemoptysis due to alveolar hemorrhage, defined as “severe pulmonary hemorrhagic leptospirosis” and characterized by a grim outcome ( 16 ), which seems to be rare. In our analysis, despite the frequency of ARF, we did not identify a specific respiratory cluster, in contrast with previous studies ( 5 , 15 ). Notably, the presence of interstitial lesions on pulmonary CT was associated with 30-day mortality in our study (Table 1 ), as previously described ( 4 , 5 , 15 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Imaging of pulmonary diffuse hemorrhagic leptospirosis typically reveals bilateral patchy peripheral infiltrates, often with a “snowflake” appearance, that can progress to confluent consolidation or a ground-glass appearance ( 11 ). The lesions are obvious in the middle and lower lobes of bilateral lungs, and the imaging manifestations are consistent with the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of reported lab-confirmed human leptospirosis cases in Colombia required admission to the ICU (30.3%) in 2015–2020. ICU admission in this study is reported in countries where leptospirosis is a health concern, such as China, were an estimated 40% of cases are admitted to the ICU [ 70 ]. Unfortunately, despite being an endemic country, human leptospirosis in Colombia is not widely known.…”
Section: Discussionmentioning
confidence: 99%